REMOVAL OF CRYSTAL VIOLET DYE FROM AQUEOUS SOLUTION BY GAMMA IRRADIATION - Rehman, Faiza; Sayed, Murtaza; Khan, Javed Ali; Khan, Hasan M. (Journal of the Chilean Chemical Society, 2017)
In this study the radiation-induced degradation of crystal violet (CV) dye under various experimental conditions has been investigated. D0.5, D0.9 and D0.99 values suggests that lower doses are required for 50%, 90% and 99% removal of CV dye when the sample solution contains excessive amount of •OH radicals. The removal efficiency of CV dye in terms of G-values was also calculated under each reaction conditions. The results showed that •OH radicals are playing effective role in the degradation of CV dye as compared to eaq‒ and •H radicals. The gamma irradiation process effectively degraded CV dye at all pH values. The organic byproducts were examined and accordingly degradation pathway was proposed.